2005
DOI: 10.1109/tasc.2005.849084
|View full text |Cite
|
Sign up to set email alerts
|

Test Results of the ITER PF Insert Conductor Short Sample in SULTAN

Abstract: A short sample of the NbTi cable-in-conduit conductor (CICC) manufactured for the ITER PF insert coil has been tested in the SULTAN facility at CRPP. The short sample consists of two paired conductor sections, identical except for the sub-cable and outer wraps, which have been removed from one of the sections before jacketing. The test program for conductor and joint includes DC performance, cyclic load and AC loss, with a large number of voltage taps and Hall sensors for current distribution. At high operatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
63
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 15 publications
5
63
0
Order By: Relevance
“…Further details on the coil design [6], strand and cable manufacturing [7]- [11], coil manufacturing [12], short sample test results [5], [13], and supporting analyses to the insert test [14]- [17] can be found in the extensive list of references quoted. [19], [20], with the necessary adaptations to the different operating conditions and PF conductor characteristics [15].…”
Section: The Pf Conductor Insertmentioning
confidence: 99%
See 4 more Smart Citations
“…Further details on the coil design [6], strand and cable manufacturing [7]- [11], coil manufacturing [12], short sample test results [5], [13], and supporting analyses to the insert test [14]- [17] can be found in the extensive list of references quoted. [19], [20], with the necessary adaptations to the different operating conditions and PF conductor characteristics [15].…”
Section: The Pf Conductor Insertmentioning
confidence: 99%
“…Short sample tests in SULTAN [5] had shown that above a current threshold ranging from 38 to 45 kA, the quench current of the PFI CICC was much below the expected strand critical current. This was attributed to the combination of the magnetic and electric field gradient in the large cross section of the cable, uneven current distribution in the short sample, impressed by the joint [21], and poor current redistribution.…”
Section: The Pf Conductor Insertmentioning
confidence: 99%
See 3 more Smart Citations